Effect of Tecoma stans (L.) Juss. ex Kunth in a Murine Model of Metabolic Syndrome - Dulce Lourdes Morales-Ferra; Miguel Ángel Zavala-Sánchez; Enrique Jiménez-Ferrer; Manasés González-Cortazar; Alejandro Zamilpa (Plants, 2022)
Metabolic syndrome is a constellation of abnormalities related to insulin resistance with an unfortunately high prevalence worldwide. Tecoma stans (L.) Juss. Ex Kunth. is a well-known medicinal plant that has been studied in several biological models related to diabetes mellitus. The aim of this study was to evaluate the effects of T. stans on a hypercaloric diet-induced metabolic syndrome model. An organic fraction obtained using liquid–liquid separation from the hydroalcoholic extract of T. stans and four subfractions of this organic fraction were administered for ten weeks to C57BL6J male mice previously fed with a hypercaloric diet. The hypercaloric diet caused changes in glucose levels (from 65.3 to 221.5 mg/dL), body weight (31.3 to 42.2 g), triglycerides (91.4 to 177.7 mg/dL), systolic (89.9 to 110.3 mmHg) and diastolic (61.6 to 73.7 mg/dL) blood pressure, and insulin resistance (4.47 to 5.16). Treatment with T. stans resulted in improvements in triglycerides (83.4–125.0 mg/dL), systolic blood pressure (75.1–91.8 mmHg), and insulin resistance (4.72–4.93). However, the organic fraction and hydroalcoholic extract produced a better response in diastolic blood pressure (52.8–56.4 mmHg). Luteolin, apigenin, and chrysoeriol were the major constituents in the most active subfractions. Treatment with T. stans, particularly a luteolin-rich organic fraction, achieved an improvement in metabolic syndrome alterations.